Insider's Guide to Outsourcing Risks and Rewards, The (CRC Press, 2009)
It is essential for a corporation to not only survive but thrive in today's global outsourcing environment. The Insider's Guide to Outsourcing Risks and Rewards is a comprehensive and accessible resource that assists an organization in deciding whether it will benefit from pursuing-or not pursuing-such an endeavor.